Parental socioeconomic status and adolescent development in Indonesia - Seonkyung Choi; Insik Min (International Journal of Adolescence and Youth)
We examine the impact of parental socioeconomic status on adolescent cognitive and non-cognitive development using data on adolescents from the 2014–15 Indonesian Family Life Survey. The analysis is relatively new for a developing country, by including non-cognitive skills and by looking at adolescents rather than young children. Parental education has a greater cognitive skills effect than parental income and job status, especially for fathers. For non-cognitive skills, parental job status is important but only for mothers. Education policy could therefore focus especially on high school completion and higher education enrolment, while employment policy could improve women’s job flexibility.